2018
DOI: 10.1039/c8an00734a
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted electrospun nanofibers for adsorption of 2,4-dinitrotoluene in water

Abstract: The detection and adsorption of nitroaromatic compounds such as 2,4-dinitrotoluene (DNT) is of great importance, but the selective detection of trace DNT in water remains a challenge. Here, we report molecularly imprinted polymer (MIP) nanofibers fabricated by electrospinning using DNT as a template molecule and poly(allylamine) as a functional macromer. The physical and chemical properties of the nanofibers were characterized by Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The high resolution XPS of C 1s ( Figure 2 c) can be divided into to four peaks at 284.2, 284.8, 286.2, and 288.2 eV, demonstrating the existence of C-Si, C-C, C-O/C-N, and C=O bonds on the surface of nanoprobe [ 43 , 44 ]. The N 1s spectrum in Figure 2 d can be deconvoluted into three peaks, ascribed to N−H at 399.4 eV, N−C at 401.5 eV, and NO 3 − at 406.6 eV, respectively [ 45 , 46 ]. These results supported that cit-Eu complex had been successfully grafted on the surface of SiCDs@mMIP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high resolution XPS of C 1s ( Figure 2 c) can be divided into to four peaks at 284.2, 284.8, 286.2, and 288.2 eV, demonstrating the existence of C-Si, C-C, C-O/C-N, and C=O bonds on the surface of nanoprobe [ 43 , 44 ]. The N 1s spectrum in Figure 2 d can be deconvoluted into three peaks, ascribed to N−H at 399.4 eV, N−C at 401.5 eV, and NO 3 − at 406.6 eV, respectively [ 45 , 46 ]. These results supported that cit-Eu complex had been successfully grafted on the surface of SiCDs@mMIP.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the static quenching was excluded by the analysis of UV spectra. The UV-Vis absorption spectra of SiCDs, TC, and the mixture of SiCDs and TC ( Figure S8 ) indicated that there was no additional absorption bond, and the position of the absorption peak was hardly changed, indicating that there was no new substance formation [ 45 ]. Moreover, the fluorescence emission of SiCDs overlapped with the absorption spectrum of TC, and it can be speculated that the fluorescence quenching may be caused by IFE or FRET [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The polymer concentration played the most crucial role during fiber formation within this study, whereby the changes in concentration led to the formation of electrospun mats of different morphologies, i.e., either beads, beaded fibers, or uniform fibers with different FD. The fiber morphology is mainly controlled by the charge carrying density, surface tension, and the viscoelasticity of the microemulsion being electrospun, which are factors mainly affected by the polymer concentration [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…This leads to a more uniform fiber morphology with increased FD. At the highest concentrations, further increase in FD is no longer observed, as the increase in viscosity and polymer chain entanglement renders the ejection of the polymer jet more difficult [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, the reported preparation methods for MIP coatings include co‐polymerization , sol‐gel technique , electrochemical method , and so on. A uniform and compact coating with high adhesive strength can be obtained by co‐polymerization method, which is most widely used.…”
Section: Introductionmentioning
confidence: 99%